From the Reed Sea to Kadesh - Jeon, Jaeyoung (Mohr Siebeck, 2022)
Cover – Title – Preface – Table of Contents – Abbreviations – I. Introduction – 1. Pentateuchal Formation Models and the Wilderness Narrative – 1.1. The Views based on the Classical Documentary Model – 1.2. The Newer Models – 1.2.1. Two-Layer Models – 1.2.2. Complex Models – 1.3. Structural Studies – 2. Scope, Formation Model, and Methodology in This Study – 2.1. Scope of the Study – 2.2. Methodology – 2.3. Literary Layers and the Formational Model in This Study – 2.4. Structure of This Study – II. Early Traditions in the Wilderness Narrative – 1. Some Early Traditions in the Wilderness Narrative – 1.1. A Strange Route from Egypt to Canaan – 1.2. A Sacred Mountain and Yhwh in the South – 1.3. The Detour and the Transjordanian Traditions – 1.3.1. The Conquest of Transjordan by Northern Israel – 1.3.2. Eastern Origins of Israel? – 1.4. Early Versions of the Wilderness Narrative – 1.4.1. The Southern Desert and Transjordan – 1.4.2. Inclusion of the Kadesh Tradition – 1.4.3. A
Description based on publisher supplied metadata and other sources
Keywords: Electronic books